Extreme space weather events of solar cycle 24: X-class solar flares and their impact on the low-latitude D-region ionosphere - Venkatesham, K.; Maurya, Ajeet K.; Singh, Rajesh; Dwivedi, Suneet (My University, 2023)
X-class solar flares, which occurred in the daytime from 2008 to 2016 during solar cycle 24, were studied for their influence on the lower ionosphere over the low-equatorial Indian region. To understand the D-region behaviour during flare events, we used the very low fre-quency (VLF) navigational transmitter NWC (19.8 kHz) signal recorded at Pryagraj, Uttar Pradesh, India. A total of seven parameters were estimated: (i) the mag-nitude of X-ray flux, (ii) VLF signal rising amplitude perturbation (SRAP), (iii) X-ray flux and NWC signal start time difference (STD), (iv) peak time difference (PTD), (v) Wait’s ionospheric parameters h′ (reference height), (vi) β (sharpness factor) and (vii) D-region electron density difference (EDD) to determine the overall effect of solar flares on the D-region. The re-sults suggest that three parameters (X-ray flux, SRAP and h′) show a decreasing trend through the linear fit line, two parameters (β and EDD) show an increasing trend, while the remaining two parameters show a mixed trend (decrease during low activity and increase during high activity). Further, the trend line during the diurnal variation shows an increasing trend for X-ray flux, PTD and h′, and a decreasing trend for SRAP, STD, β and EDD. Deviation in the case of individual events may indicate the dependence of these parame-ters on the seasons as well. The present study will pro-vide the base for more robust analysis and modelling work in the future to understand the complexity of ion-ospheric change during flare events, and to develop a predictive model for space weather mitigation.
Keywords: D-region ionosphere; Space weather; Solar cycle; Solar flares; Trend line; VLF waves